Symptom Exacerbation and Adherence to Antiretroviral Therapy During the Menstrual Cycle: A Pilot Study (Hindawi Limited, 2006)
Our objective is to investigate the relationship between drug and menstrual cycle symptoms in HIV+ women receiving antiretroviral therapy (HAART). Interviews were done for 12 weeks with 54 HIV+ women receiving HAART. Patients were asked if they experienced any of 28 symptoms associated with HAART and the menstrual cycle and about HAART adherence. Weeks were divided into menstrual weeks (MWs), premenstrual weeks (PWs), and other weeks. Women reported more bloating ( P=.02 ) and cramps ( P=.001 ) during MWs. Skin problems ( P=.08 ) and breast tenderness ( P=.03 ) were experienced during PWs. Feeling tired/loss of energy ( P=.05 ), joint pain ( P=.02 ), and chills ( P=.03 ) were higher in non-MW/PWs. Women were slightly less adherent during the MWs (89%) than PWs (94%) and other weeks (93%). Feeling sad or depressed ( P=.01 ) was associated with nonadherence. Experiencing certain symptoms associated with both the menstrual cycle and HAART drugs was related with nonadherence.